Validation study of the pediatric allergic rhinitis quality of life questionnaire - Mavroudi,A; Chrysochoou,EA; Boyle,RJ; Papastergiopoulos,A; Karantaglis,N; Karagiannidou,A; Xinias,I; Farmaki,E; Hatziagorou,E; Kirvassilis,F; Kourentas,G; Tsanakas,J; et al. (Asian Pacific Journal of Allergy and Immunology, 2016)
Background: The Paediatric Allergic Rhinitis Quality of Life Questionnaire (Ped-AR-QoL) is the first tool developed for the assessment of health-related quality of life (QoL) in Greek children with allergic rhinitis (AR). Objective: The aim of the current study was to validate the child and parent forms of the Ped-AR-QoL in children aged 6-14 years-old who suffered from AR and were followed in a pediatric allergy clinic. Methods: The Ped-AR-QoL, which was completed by 112 children and their parents, was correlated to the generic QoL questionnaire (Disabkids), which is already valid in Greece for children with chronic disorders, as well as with expert opinions on the severity of disease. Results: The Ped-AR-QoL child and parent forms had very good internal consistency (α values of 0.797 and 0.872, respectively), while there was a moderate positive correlation of the disease-specific questionnaire with most of the subscales of the generic questionnaire. There has been a statistically significant association between the Ped-AR-QoL and the expert perception of disease severity. Conclusions: The Ped-AR-QoL had very good reliability and convergent validity when compared with the generic Disabkids QoL. The significance of the association between the disease-specific questionnaire and the expert opinion is an important finding validating the questionnaire. The Ped-AR-QoL may become a helpful tool which can be used in everyday clinical practice by clinicians and it may also be used for assessing therapeutic interventions in clinical trials.